Migraine management: an update for the 2020s. Issue 7 (25th July 2022) - Eller, Michael; Cheng, Shuli
Abstract: Migraine is a common malady cutting across socioeconomic and ethnic divides in Australia. It is typically diagnosed late with significant impact on quality of life. Management options have emerged over the past several years that promise simpler treatment regimens with less potential for side‐effects. The development of rationally designed migraine preventives is the most significant advance in treatment since the development of the triptans and delivers significant hope to many headache sufferers.